#### Answer

$c=-\frac{1}{2}$.

#### Work Step by Step

Since $y=x-2+e^{cx}$, then we have $y'=1+ce^{cx}$. Now, by substitution, we get
$$2y'+y=2+2ce^{cx}+x-2+e^{cx}=x$$
which leads to
$$(2c+1)e^{cx} =0$$
that is, $2c+1=0$ and hence $c=-\frac{1}{2}$.

Chegg costs money, GradeSaver solutions are free!

Published by
W. H. Freeman

ISBN 10:
1464125260

ISBN 13:
978-1-46412-526-3

$c=-\frac{1}{2}$.

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.